PREPARATION AND CHARACTERIZATION OF HYBRID CATALYSTS FOR CO2 HYDROGENATION REACTION - Ramli, M. Z.; Mohd Zabidi, N. A.; Chong, F. K (Malaysian Solid State Science and Technology Society, 2007)
Hybrid catalytic system comprising different ratios of CuO/ZnO/Al2O3: zeolite have been formulated and characterized. The methanol-synthesis catalyst, Cu/ZnO/Al2O3 (CuO:ZnO:Al2O3 = 50:45:5), was prepared by a co-precipitation method. The copper catalyst was physically mixed with ZSM-5 zeolite at ratios of 1:1, 1:2 and 2:1. The hybrid catalysts were characterized using x-ray diffraction method (XRD), temperature-programmed reduction (TPR) and temperature-programmed desorption (TPD) with ammonia. The hybrid catalysts produced two different acid sites as depicted by the ammonia TPD profiles. A TPD peak at 300°C indicated a weak acid site and a stronger acid site were observed at 550 °C. The hybrid catalyst with a 1:1 weight ratio has the highest acid strength and absorbed the most hydrogen. This hybrid catalyst may be used in the hydrogenation of CO2 to methanol and dimethyl ether.